VOTUM: Secure and Transparent E-Voting System - Egocheaga, Joaquin (2024)
Elections are an essential part of citizens’ rights, and they are also conducted in universities and colleges to ensure transparent selection of ideal authorities while preventing identity fraud and information loss among voters. It is worth noting that Internet voting has gained significant attention in recent years, with many organizations worldwide planning to experiment with and implement it. To address these challenges, we propose VOTUM, a free fraud e-voting system that incorporates two authentication methods: facial recognition and one-time password (OTP). Additionally, the system employs two cryptographic algorithms to encrypt voters’ information throughout the voting process and generates a unique code to verify the successful casting of votes. VOTUM's design is creative, flexible, colorful, and animated, aiming to encourage students and professors to fulfill their civic duty by participating in elections. Through interviews conducted with 31 students and university professors, we achieved a 90% trust level and a 15% margin of error to assess satisfaction with transparency, trust, and user experience within the VOTUM system. The results indicated a satisfaction level of over 90%, showing the significant contribution of this research in enhancing trust and transparency in the voting processes of universities and colleges.